Recent advances of highly selective CDK4/6 inhibitors in breast cancer - Xu, Hanxiao; Yu, Shengnan; Liu, Qian; Yuan, Xun; Mani, Sridhar; Pestell, Richard G.; Wu, Kongming (Journal of Hematology & Oncology, 2017)
Uncontrolled cell division is the hallmark of cancers. Full understanding of cell cycle regulation would contribute to promising cancer therapies. In particular, cyclin-dependent kinases 4/6 (CDK4/6), which are pivotal drivers of cell proliferation by combination with cyclin D, draw more and more attention. Subsequently, extensive studies were carried out to explore drugs inhibiting CDK4/6 and assess the efficacy and safety of these drugs in cancer, especially breast cancer. Due to the insuperable adverse events and the less activity observed in vivo, the drug development of the initial pan-CDK inhibitor flavopiridol was consequently discontinued, and then highly specific inhibitors were extensively researched and developed, including palbociclib (PD0332991), ribociclib (LEE011), and abemaciclib (LY2835219). Food and Drug Administration has approved palbociclib and ribociclib for the treatment of hormone receptor-positive, human epidermal growth factor receptor 2-negative advanced or metastatic breast cancer, and recent clinical trial data suggest that palbociclib significantly improved clinical outcome when combined with letrozole or fulvestrant. Besides, the favorable effects of abemaciclib on prolonging survival of breast cancer patients have also been observed in clinical trials both for single-agent and combination strategy. In this review, we outline the preclinical and clinical advancement of these three orally bioavailable and highly selective CDK4/6 inhibitors in breast cancer.